Characteristics of Persons Treated for Hepatitis C Using National Pharmacy Claims Data, United States, 2014–2020 . (16th February 2022) - Teshale, Eyasu H; Roberts, Henry; Gupta, Neil; Jiles, Ruth
Abstract: Using national pharmacy claims data for 2014–2020, 843 329 persons were treated for hepatitis C at least once. The proportion treated increased annually among persons aged <40 years, insured by Medicaid, and treated by primary care providers. Monitoring hepatitis C treatment is essential to identify barriers to treatment access.